Prevalence, antibiotic resistance, enterotoxin genes, biofilm formation, and agr typing of Staphylococcus aureus from raw milk and cheese - Yüksel Yence, D. (Polish Journal of Veterinary Sciences, 2026)
In this study, Staphylococcus aureus was detected in 46% of raw milk and 10% of cheese samples collected in Edirne, Türkiye. All isolates carried the sec and seg enterotoxin genes, while 39% harbored sed, 7% seh, and only 4% of isolates carried either sea or sei. A total of 25% of the isolates exhibited multidrug resistance. The highest resistance rate was observed against penicillin (39%), followed by kanamycin (18%), tetracycline (14%), clindamycin (11%), chloramphenicol and rifampin (7%), and trimethoprim-sulfamethoxazole and gentamicin (4%). Methicillin resistance was found in 11%, and mecA was identified in two isolates. All isolates formed biofilms at 22°C and 37°C, and 82% also at 4°C. Agr typing showed that 21% of isolates belonged to group I, 21% to group II, and 11% to group III, while no group IV isolates were detected. These findings demonstrate that enterotoxigenic, antimicrobial-resistant, and biofilm-forming S. aureus isolates from dairy products may persist along the food chain and represent a potential public health risk, underscoring the importance of continuous microbiological monitoring and preventive strategies within a One Health framework.